2021
DOI: 10.21149/12696
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance, refusal and hesitancy of Covid-19 vaccination in Mexico: Ensanut 2020 Covid-19

Abstract: Objective. To estimate the willingness to vaccinate against Covid-19 (acceptance) in the Mexican population and to iden­tify socioeconomic factors associated with vaccine hesitancy and refusal. Materials and methods. We estimated the acceptance, refusal and hesitancy proportions using data from the Covid-19 National Health and Nutrition Survey conducted from August to November 2020. Factors associated with re­fusal and hesitancy were explored using multinomial logistic regression. Results. Covid-19 vaccination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 14 publications
8
29
3
3
Order By: Relevance
“…A study in the United Kingdom about the COVID-19 vaccine found uptake was generally high and hesitancy concentrated on females and subgroups characterized by lower education and some ethnic minorities [ 9 ]; a relatively low proportion of older adults (4.1–14.3%) expressed it was unlikely they will receive the shot. In Mexico, even though older adults have a higher risk of COVID-19 mortality, a population study conducted between September and November 2020 found that older adults –especially female– had the lowest vaccine acceptance between age-groups (54.0%); acceptance increased with education and having formal employment, and Mexico City was the state with the highest percentage of vaccine acceptance (69.3%), still low in comparison with other countries [ 10 ].…”
Section: Survey and Resultsmentioning
confidence: 99%
“…A study in the United Kingdom about the COVID-19 vaccine found uptake was generally high and hesitancy concentrated on females and subgroups characterized by lower education and some ethnic minorities [ 9 ]; a relatively low proportion of older adults (4.1–14.3%) expressed it was unlikely they will receive the shot. In Mexico, even though older adults have a higher risk of COVID-19 mortality, a population study conducted between September and November 2020 found that older adults –especially female– had the lowest vaccine acceptance between age-groups (54.0%); acceptance increased with education and having formal employment, and Mexico City was the state with the highest percentage of vaccine acceptance (69.3%), still low in comparison with other countries [ 10 ].…”
Section: Survey and Resultsmentioning
confidence: 99%
“…Two nationally representative surveys on COVID-19 vaccination are available in Mexico. One, conducted from August to November 2020, identified 62.3% acceptance, 28.2% refusal, and 9.5% hesitancy ( 8 ). The second, conducted in November 2020, reported 82% acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…In January 2021, Argote-Tironi et al 30 conducted an online survey across six Latin American countries, including Mexico; only 62.5% of the participants strongly agree/agree with the statement, “If a vaccine were available to me now, I would get vaccinated” and this percentage is in accordance with a 62.3% of COVID-19 VA described in a nationally representative sample of the Mexican population. 31 …”
Section: Discussionmentioning
confidence: 99%